PENGARUH PROMOSI DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN BATIK SEKAR JATI BY RIRIN - Usman Maulana; Rohmad Prio Santoso (CV. KAMPUS AKADEMIK PUBLISING, 2024)
promotion is any form of persuasive communication designed to inform customers about a product or service and to influence them to buy the goods or services which includes publicity, personal selling and advertising, Brand equity is the strength of the added value that a product and service has on consumers, which consumers may think, feel, and do, brand equity is defined as a set of legacies and liabilities related to using a brand that increases or decreases the value given by the goods or services in a company or customer, purchasing decisions are an approach to solving problems in human activities to buy goods or services in fulfilling their desires and needs which consist of recognizing needs and desires, searching for information, evaluating alternative purchases, purchasing decisions and post-purchase behavior